PERCEPTION OF HEALTH WORKER ON INTEGRATION OF NURSING EDUCATION AND NURSING SERVICES AT PROVINCIAL HOSPITAL, JANAKPUR - Kumari Yadav, Poonam; Yadav, Punita; Sah, Shivani; Dahal, Laxmi (Journal of Chitwan Medical College, 2024)
Background: Integration in nursing is a challenge. Integration of nursing results in improved patient care, emotional safety, reduced workload and better communication among various disciplines. The aim of this study was to assess the perception of health workers on integration in nursing education and nursing services. Methods: A descriptive cross-sectional study was conducted among 158 health working in Provincial Hospital, Janakpurdham, Nepal. The samples were selected using Convenience sampling technique. Self-administered questionnaire on three-point Likert Scale was used for data collection to assess the perception of health care providers on integration of nursing education and nursing services. Data were analyzed in Statistical Package for Social Science (SPSS version 26) using descriptive statistics. Results: The perception of health worker regarding integration of nursing education and nursing services was high in 74.5% medium in 18% and low in 7.5% of the participants. The doctors and teaching faculties have high perception and the nursing staff have medium perception on integration of nursing services and nursing education. Conclusions: The overall perception of health worker on integration of nursing education and nursing services were high. Males have more high perception compared to female. The teaching faculties have more high perception compared to non-teaching samples.